2023
DOI: 10.1039/d3gc01700a
|View full text |Cite
|
Sign up to set email alerts
|

Utilising bio-based plasticiser castor oil and recycled PLA for the production of conductive additive manufacturing feedstock and detection of bisphenol A

Abstract: The production of electrically conductive additive manufacturing feedstock from recycled poly(lactic acid) (rPLA), carbon black (CB), and bio-based plasticiser castor oil is reported herein. The filament was used to print...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 28 publications
4
22
0
Order By: Relevance
“…The onset temperature of thermal degradation and conductive filler contents, where applicable, are presented in Table S1. It can be seen that the rPLA used throughout this study had an average onset of degradation temperature of 304 ± 4 °C, which showed good agreement with previous work. , As previously reported, castor oil produced an onset temperature of 250 ± 3 °C . The bespoke graphite/CB filament produced an average onset of degradation temperature of 283 ± 4 °C, which indicated that the conductive carbon fillers provided a stabilizing effect by acting as a barrier for gas diffusion out of the polymer, slowing the rate of decomposition .…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…The onset temperature of thermal degradation and conductive filler contents, where applicable, are presented in Table S1. It can be seen that the rPLA used throughout this study had an average onset of degradation temperature of 304 ± 4 °C, which showed good agreement with previous work. , As previously reported, castor oil produced an onset temperature of 250 ± 3 °C . The bespoke graphite/CB filament produced an average onset of degradation temperature of 283 ± 4 °C, which indicated that the conductive carbon fillers provided a stabilizing effect by acting as a barrier for gas diffusion out of the polymer, slowing the rate of decomposition .…”
Section: Resultssupporting
confidence: 90%
“…The graphite/CB filament exhibited excellent printability, as shown for the lollipop-shaped AMEs, Figure D, where no additional extrusion rate was required to get a high-quality print. In comparison, the CB-only filament required increased extrusion rates to achieve a nonporous print surface …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations